Back to School: Towards a New Agenda for the History of Education (review) - Gaffield, Chad (Université d'Ottawa | University of Ottawa, 1986)
T H E CENTRAL HISTORIOGRAPHICAL QUESTION of the 1980s results from the research activity of the 1970s: What are the relationships among the new subfields of social history and between these subfields and the traditional "grand events"? Historians of various orientations have given this question a great deal of consideration in recent years and not surprisingly have come to quite different conclusions. Nonetheless, one trend is clear. The talk is now of synthesis, of integration, of coherence. In the 1970s, the development of new fields of social history represented an expanding historical consciousness; now this development is often discussed in terms of fragmentation. The 1980s has become a decade of nostalgia, of longing for a time when writing about the past seemed a lot simpler and the results more fun to read.